Imaging the Mahout structure at the Oman desert with the aid of geophysical observations - Sobhi Nasir; Nikos Economou; Nikos Economou; Khalil Al Hooti; Talal Al Hosni (Frontiers in Earth Science)
Geophysical methods may provide crucial information for the characterization of buried impact structures. In this study, we report and comment on the results of the geophysical survey of an elliptical-shaped structure near Mahout at Oman’s central desert. Geophysical models describe the variation in the physical properties of this structure’s subsurface in terms of density, magnetic susceptibility, and electrical resistivity of the formations buried under the desert sand. For the two former physical properties, a 3D inversion scheme was utilized, while for the latter, the very-low-frequency electromagnetic (VLF-EM) method and 2D inversion were involved for the first time in a similar study. The resultant models are in good agreement for imaging a generally bowl-shaped structure buried under the desert sand with a low resistivity (<40 Ohmm), highly magnetic (magnetic susceptibility 0.03–0.08 SI), and mixed density center (2.2–3.2 g/cm3). The results of the integrated geophysical survey at Mahout enhance the information about the applicability of the specific geophysical techniques at structures buried by sandy formations with less than 1-km diameter, which, currently, mostly comes from large-scale impact craters (>100 km), and confirm that such a multi-geophysical approach can be successful for imaging similar structures.